Welfare from the Perspective of Ayatullah JawÁdÐ ÀmulÐ - Najaf Lakzai (حکمت اسرا)
Welfare is one of the most important components of society. The focus of this article is to investigate this concept according to the views of AyatullahJawÁdÐÀmulÐ. Considering that the respected scholar has not brought up this topic independently in any of his works, the author has extrapolated the views of Ayatullah JawÁdÐ through a process that essentially relies on understanding, analyzing, and examining the works of the respected thinker within the framework of his intellectual school of thought. For this reason, the theoretical framework of the fourfold causesin Islamic philosophy comprises the theoretical basis of this research through which this matter is examined. Since welfare is a possible phenomenon, its causes can be analyzed in terms of material, formal, efficient, and final causes. Based on AyatullahJawÁdÐÀmulÐ’s philosophical methodology in the Transcendental Theosophical school of thought, the author has attempted to compare AyatullahJawÁdÐ’s transcendental views on welfare with the ordinary mediocre view of welfare that is prevalent todayusing the fourfold criteria mentioned above.